(untitled) (Research, Society and Development, 2022)
Business transactions are an important relationship and evolution tool that man has learned to live with and which will hardly cease to exist even in the increasingly modern world. We cannot deny that our evolution was and still is the result of the socialization of a people who learned from the beginning, and still learns, to relate mainly due to the fact that they maintain commercial relations in every way, whether through services or through exchange of material goods. Since the most remote times, with the culture of barter, including, for example, salt, hunting tools, precious metals, we have been improving objects that we valued to serve as a means of exchange for other objects of value as well, all this even before of there being a State, that is, an imposed law, but by the own will and definition of the creative possessing parties involved. In today’s world, we already have several types of ways to carry out commercial transactions, whether physical currency, checks, magnetic cards, those with said balances controlled by banking institutions authorized by the State to operate and with well-established rules. More recently we have at our disposal a new option to carry out commercial transactions, totally digital, the cryptoactive ones, being the most popular and pioneer “bitcoin”, but we still ask ourselves: is it safe? it’s trustable? is it a threat to the end of the traditional physical currency we are used to? will it be another form of population control?